The study of antibacterial activity in enteric pathogens of Roselle (Hibiscus sabdariffa Linn.) by broth micro-dilution method - Bajaree Jantrapanukorn, Sawanya Pongpraritt, Pannapa Powthong, Thanet Pheungphu (Journal of Applied Pharmaceutical Science, 2017)
The crude water extract of Roselle (Hibiscus sabdariffa Linn.) was determined for its antibacterial activities on 6 bacterial reference strains and 16 isolates of enteric pathogens. Determination of minimum inhibitory concentrations(MICs) by broth microdilution method with final concentration of Roselle extract between 200-3.125 mg/ml showed that Roselle extract could inhibit the growth of bacterial reference strains at MICs 25 mg/ml on Aeromonas veronii biogroup sorbria ATCC 9071, MICs 50 mg/ml on Yersinia enterocolitica ATCC 9610 and MICs 100 mg/ml on Aeromonas caviae ATCC 15468, Aeromonas hydrophila ATCC 35654, Vibrio parahaemolyticus ATCC 17802, Vibrio vulnificus ATCC 27562. Roselle extract also exhibited its antibacterial activities on enteric pathogens giving the MICs of 25 mg/ml on Edwardsiella tarda and Yersinia pseudotuberculosis, the MICs of 50 mg/ml on Plesiomonas shigelloides, Salmonella arizonae, Salmonella choleraesuis, Salmonella paratyphi A, Salmonella Typhi, Shigella boydii, Shigella dysenteriae, Shigella flexneri, Shigella sonnei, Vibrio cholerae and Yersinia enterocolitica, the MICs of 100 mg/ml on Aeromonas caviae, Aeromonas hydrophila and Salmonella enteritidis. The data indicated that Roselle extract could produce antibacterial activities against enteric pathogens at various concentrations. The extract should be further study to use as antibacterial agent for controlling these organisms.
Keywords: Roselle, Hibiscus sabdariffa Linn., Minimal Inhibitory Concentration (MIC), Enteric bacteria pathogen.